Beyond beans: examining the effects of COVID 19 on other food value chains in Sub-Saharan Africa - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2021)
The pandemic has disrupted input supply systems in almost all countries studied, causing low use of yield enhancing techologies such as improved seed and inorganic fertilizer. Measures put in place to curb transmission of the deadly virus have created labour shortages of workers at farm level and business level leading to higher labour prices. The functioning of the food supply chains have been disrupted by COVID-19 containment measures causing low prices in production hubs and high food prices in urban and peri-urban areas. The pandemic threatens the already dire food security situation in Eastern and Southern Africa.